Mandatory substance use treatment for justice-involved persons in Germany: a systematic review of reoffending, treatment and the recurrence of substance use outcomes - Tomlin, Jack; Meise, Esther; Wegner, Juliane; Völlm, Birgit (Frontiers in Psychiatry, 2024)
Many jurisdictions implement mandatory substance use treatment for justice-involved persons. Germany is one such country; however, debates about the appropriateness and effectiveness of this disposal abound. Very little attention has been paid in the international literature to patients receiving mandatory treatment in Germany. This systematic review synthesizes research on patients receiving substance use treatment in forensic hospitals under §64 of the German Penal Code with regard to three primary outcomes: treatment completion, reoffending, and the recurrence of substance use. Forty-five publications reporting on 36 studies were reviewed; publication dates ranged from 1988 to 2023. On average, 47% of patients did not successfully complete treatment, compared to 45% who did. Average follow-up reconviction rates were higher than in mentally ill and general offender populations as reported elsewhere. Approximately half of all patients reused substances during treatment. Suggestions for future research, including a focus on strength-and recovery-based indicators, and harmonizing routine outcomes measurements, are given.